GLOBALIZATION AND ECOLOGY - Monge, Daniel Camacho (2006)
The process of globalization reaches all dimensions ofSociety and ecology is no exception. It is not about demonizing or sanctifying globalization. It goes without saying that it is neither negative nor positive in itself, but depends on the course that is given to it. Of allways humanity has always been in the process of globalization.What, if not that was the Roman expansion, or that of the Arab culture, or thecrusades, or the Hellenic-Macedonian rule with Alexander, or the empireof Charlemagne, or the Napoleonic expeditions, or the conquest of America by Europeans and a long etcetera.